Competitividade: uma análise comparativa dos custos entre o aperfeiçoamento presencial e a distância numa empresa do setor de saúde - Santos, Marcelo Henrik Silva dos (2005)
This study presents a comparative analyzes of costs between two modalities of professional education: the first one is accomplished within the presence of a person who is specialized in a certain area and the second is made at a distance. Such work was accomplished in a company related to the health sector. For so, it presents knowledge and information management as a factor of competitiveness, emphasizing its importance for the efficiency of the personnel as well as about the necessities the companies have of creating, at the present situation, mechanisms which allow the development of the individual capacity of such employees, as well as the fast circulation of the knowledge acquired within the company in order to disseminate as well as to protect it. The theoretical basis for the present study is the reduction of costs as one of the competitive advantage sources. As for literature, the theory is based specially in Michael Porter. The main aim of the present study is to identify which factors that are peculiar to the improvement at a distance may generate a reduction of costs for the company Med, if compared to the improvement with the presence of the specialist. To draw the conclusion about which factors of improvement at a distance contribute for the reduction of costs, an analysis of the costs generated by the present form of improvement performed by the company which is being researched must be made. Then, a simulation with the costs of improvement made at a distance must be accomplished. One of the conjectures of the present research is that with the adoption of the method of improvement at a distance the company which is being researched will have a reduction of costs. Characterized as of the exploratory nature, in this study, it was used for the acquisition of information a semi-structured interview along with the ones who were involved with the aspects of costs related to the professional education in the company which was researched. As far as the reduction of cost was concerned, the improvement at a distance is shown as a great tool for the development of the personnel embracing a bigger contingent of people at a lower cost and generating higher competitivity. The result of the work showed the viability of the company which was researched by substituting its model of development of people for the improvement at a distance. According to what was shown here, the content of the research may be used as a reference for future researches on the same subject. It may also facilitate the application of the research in another sector or industry. The research approached the subject competitivety related to a model of development which was growing in the companies. That is, the improvement at a distance (IAD). With the accomplishment of this study we hope to facilitate the taking of a decision by the company which was studied in relation to the model of improvement to be adopted, as well as to visualize better the composition of cost of the present model of improvement of personnel.